Study of multi-domain switching dynamics in negative capacitance FET using SPICE model. (September 2021) - Gaidhane, Amol D.; Verma, Amit; Chauhan, Yogesh Singh
Abstract: In this paper, we study the multi-domain switching dynamics for a metal–ferroelectric–insulator–semiconductor (MFIS) type negative capacitance Fin Field Effect Transistor (NC-FinFET) for a 10 nm technology node. To study its characteristics, we develop a SPICE model for multi-domain NC-FinFET. Our proposed model is based on Feynman's pedagogical model of microscopic origin of ferroelectricity. We develop this model using the positive feedback mechanism for dipole–dipole interactions in the ferroelectric material in conjugation with the BSIM-CMG model for the underneath FinFETs. This study reveals that the drain current achieved in a multi-domain case is lower than the mono-domain case. The negative differential resistance (NDR) effect in transistor characteristics is more pronounced in multi-domain NC-FinFET compared to the mono-domain case. Increasing variation in individual domain parameters of the ferroelectric material i.e., coercive voltage ( V C ) and remnant polarization ( P R ), further lowers the drain current with a hysteresis in the drain current characteristics in the multi-domain NC-FinFET.